Effect of post-milking treatment on teat skin and milk microbial diversity of dairy cows - Verdier-Metz I.; Pradel P.; Monsallier F.; Montel M.C. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
Microbial diversity is one of the specificities of traditional raw milk cheeses. It depends on both milk microbiota and microbial dynamics during manufacturing and ripening. The microbial composition of milk is not clearly understood yet; it depends on direct and indirect sources which vary according to herd management (feed, herd size, lactation rank, etc.), farm environments (litter, dung) and milking management (udder microbial community). The surface of cow teats has been described as a source of microorganisms for milk. Thus, it can be hypothesized that practices modifying the teat skin microbiota could be a lever to increase qualitatively and quantitatively the microbial diversity in milk. To check this hypothesis, the composition of microbial species of the teats of dairy cows that received three post-milking treatments (iodine, glycerol, no products) over the lactation was compared. Teat microbiota was also compared to the microbial composition of the corresponding milk. Teat microbiota was highly dominated by ripening bacteria whereas that of milk was well balanced between the different microbial groups. Forty-three microbial genera were identified on the surface of the teat against 34 in milk: 20 genera were common. The post-milking treatment affected mainly the count of ripening bacteria of teat surface whereas it had no effect on milk microbiota. The count of other microbial populations was not modified whatever the treatment.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)